Cathodoluminescence from Amorphous and Nanocrystalline Nitride Thin Films Doped with Rare Earth and Transition Metals - Maqbool, Muhammad; Jadwisienczak, Wojciech M.; Kordesch, Martin E. (IntechOpen, 2012)
None